Implementasi Manajemen Bandwidth Per Connection Queue (PCQ) untuk Meningkatkan Kualitas Layanan Jaringan Sekolah - Moh. Iqbal Maulidani; Miftahur Rahman; Ginanjar Abdurrahman; Moh. Dasuki; Luluk Handayani (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2026)
Along with the increasing use of the internet in schools, stable and evenly distributed network Quality of Service (QoS) has become essential. The use of online learning applications, web-based administration systems, and Academic Competency Tests (TKA) increases network traffic, especially during peak hours, requiring effective bandwidth management. This study implements the Per Connection Queue (PCQ) method on a MikroTik router to distribute bandwidth automatically and proportionally across the network of SMP Negeri 3 Balung, preventing excessive bandwidth usage by certain users and maintaining stability during traffic spikes. The results show that before PCQ implementation, bandwidth distribution among clients was uneven. After implementing PCQ with a total bandwidth of 50 Mbps, bandwidth was automatically and evenly distributed among active clients. QoS analysis using Wireshark indicates that throughput increased from 654 Kbps to 764 Kbps, delay decreased from 12.93 ms to 10.63 ms, and packet loss remained at 0%. The implementation of PCQ-based bandwidth management proved effective in improving both bandwidth fairness and overall network service quality at SMP Negeri 3 Balung.